FAHR’S SYNDROME SECONDARY TO NON-SYNDROMIC PRIMARY HYPOPARATHYROIDISM - Low, Chee Koon; Devaraja, Vanusha; Abas, Syarifah Syahirah Syed; Yong, Fei Bing; Ismail, Ilham; Mahadi, Mahrunnisa; Mustafa, Norlaila; Wahab, Norasyikin A. (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Fahr’s syndrome is a rare neurological disorder character- ized by abnormal calcium deposits in the brain, particu- larly in the basal ganglia. The aetiology can be primary or secondary, with endocrinopathies being the most common cause. We report a case of Fahr’s syndrome in which the patient developed seizures and ECG changes due to severe hypocalcemia. CASE A 29-year-old female with underlying type 2 diabetes, psoriasis, and cognitive delays presented with an episode of generalized tonic-clonic seizure along with perioral numbness, skin redness and peeling for one week. Medical records showed her corrected calcium was less than 1.9 mmol/L for over a decade. There was no history of neck surgery or radiation, nor similar conditions in her family. She had no dysmorphic features but was septic with a capillary glucose of 29.5 mmol/L. ECG revealed prolonged QT interval of 516 Msec. Laboratory results showed profound hypocalcemia of 1.28 mmol/L, hypomagnesemia of 0.65 mmol/L and normal phosphate level. Intact PTH and 25-hydroxy-vitamin D levels were low, at 0.485 pmol/L and 24.5 nmol/L, respectively. Her brain CT scan showed cerebral atrophy with extensive intracranial calcifications, features which were consistent with Fahr’s syndrome. Other evaluations did not suggest infiltrative or autoimmune disorders. There was no cataract or nephrolithiasis as a result of prolonged hypocalcemia. A multidisciplinary team managed her in the ICU with a diagnosis of severe sepsis secondary to erythrodermic psoriasis with superimposed bacterial infection. One week later, she was discharged well with calcium carbonate 1 gram thrice daily and calcitriol 0.5 mcg twice daily. No genetic test was performed due to financial constraints. CONCLUSION This case underscores the importance of timely diagnosis of primary hypoparathyroidism to prevent long-term complications. There are no established guidelines for the radiological surveillance intervals in Fahr’s syndrome, and individualized management remains crucial in caring for patients with this condition.